The Effectiveness of SP4N-LAPOR-Based Complaints! At the Department of Communication and Information Technology of Tasikmalaya City - Fitri Gupitasari; Muhammad Khoirul Anwar (Department of Public Administration, 2022)
When the public service process is still not maximized, the community will submit a complaint report to the Government on the suggested complaints from the community regarding public services that have not been effective. The presence of SP4N-LAPOR! is a need for a system that can integrate all complaints management in government agencies, because complaints cannot be managed partially. The purpose of this study was to determine the effectiveness of SP4N-LAPOR! at the Department of Communication and Information of the City of Tasikmalaya. This study uses the theory of Sedarmayanti (2009) regarding the effectiveness of the program with 4 indicators, namely: Input, Production Process, Output (Output), Productivity. Using descriptive research methods with a qualitative approach. Data collection techniques by observation, interviews, and documentation. Data analysis used Miles and Huberman (1984) in Sugiyono (2019), namely data collection, data reduction, data presentation and conclusion drawing/verification. The result of this research is that the complaints based on SP4N-LAPOR! has been effective in accordance with the existing mechanism in the SOP, but there are still obstacles, namely limited human resources and employee understanding and not optimal in conducting socialization.